The role of gut microbiota in the pathogenesis of diverticular disease: where are we now? - Antonio Tursi; Alfredo Papa (Genome Medicine)
Abstract Diverticular disease (DD) is widespread worldwide. The role of gut microbiota (GM) in DD is not entirely understood.  Here we discuss the significance of the current knowledge on GM in the different stages of DD and how crucial these acquisitions are for designing diagnostic and therapeutic trials in this field.